Furosemide as a factor to deteriorate therapeutic efficacy of tolvaptan in patients with decompensated cirrhosis. Issue 12 (21st September 2020) - Uchida, Yoshihito; Inao, Mie; Tsuji, Shohei; Uemura, Hayato; Kouyama, Jun‐ichi; Naiki, Kayoko; Sugawara, Kayoko; Nakao, Masamitsu; Nakayama, Nobuaki; Imai, Yukinori; Tomiya, Tomoaki; Mochida, Satoshi
Abstract : Aim: To optimize the therapeutic strategy for patients with decompensated cirrhosis manifesting hepatic ascites and/or edema, factors affecting the outcome of patients receiving tolvaptan were evaluated. Methods: The subjects were 165 patients receiving tolvaptan including 116 patients (70%) also treated with furosemide. The therapeutic efficacy of tolvaptan was defined as "effective" when a body weight reduction of 1.5 kg or more was obtained within 1 week. The long‐term outcome was defined as "favorable" when the ascites‐related events‐free duration was prolonged following tolvaptan treatment, compared with that before treatment, or ascites‐related events were absent for at least 120 days during treatment based on the hazard function analysis. Results: Tolvaptan was effective in 115 patients (70%). Among them, the long‐term outcome was evaluated in 99 patients and was favorable in 70 patients (71%). A multivariate analysis revealed that the serum blood urea nitrogen levels at baseline (odds ratio 0.960 per +1 mg/dL, P  = 0.021) and the type of tolvaptan initiation (planned vs. emergent; 3.695, P  < 0.001) were associated with therapeutic efficacy, while the furosemide dose (0.280 per +20 mg/day, P  = 0.014) and previous ascites‐related events (0.074, P  < 0.001) were associated with the long‐term outcome. Receiver operating curve analyses identified the optimal cut‐off values for the furosemide dose as 15 mg/day ( P  < 0.001). Furthermore, the cumulative survival rates in patients receiving furosemide at 15 mg/day or less were significantly higher than those in the remaining patients ( P  = 0.048). Conclusion: Furosemide given at baseline contributed to an unfavorable outcome in patients receiving tolvaptan; consequently, tolvaptan should be given before increasing the furosemide dose.